A novel electro conductive graphene/silicon-dioxide thermo-electric generator - Rahman, Mohammed Ataur; Abdi, Yusuf (IOP Publishing, 2017)
Thermoelectric generators are all solid-state devices that convert heat energy into electrical energy. The total energy (fuel) supplied to the engine, approximately 30 to 40% is converted into useful mechanical work; whereas the remaining is expelled to the environment as heat through exhaust gasses and cooling systems, resulting in serious green house gas (GHG) emission. By converting waste energy into electrical energy is the aim of this manuscript. The technologies reported on waste heat recovery from an exhaust gas of internal combustion engines (ICE) are thermoelectric generators (TEG) with finned type, Rankine cycle (RC) and Turbocharger. This paper has presented an electro-conductive graphene oxide/silicon-dioxide (GO-SiO2) composite sandwiched by phosphorus (P) and boron (B) doped silicon (Si) TEG to generate electricity from the IC engine exhaust heat. Air-cooling and liquid cooling techniques adopted conventional TEG module has been tested individually for the electricity generation from IC engine exhausts heat at the engine speed of 1000-3000rpm. For the engine speed of 7000 rpm, the maximum voltage was recorded as 1.12V and 4.00V for the air cooling and liquid cooling respectively. The GO- SiO2 simulated result shows that it's electrical energy generation is about 80% more than conventional TEG for the exhaust temperature of 500°C. The GO-SiO2 composite TEG develops 524W to 1600W at engine speed 1000 to 5000 rpm, which could contribute to reduce the 10-12% of engine total fuel consumption and improve emission level by 20%. .